Dynamics of site juxtaposition in supercoiled DNA - Jing Huang; Tamar Schlick; Alexander Vologodskii (2001)
Juxtaposition kinetics between specific sites in supercoiled DNA is investigated at close to physiological ionic conditions by Brownian dynamics simulations. At such conditions, supercoiled DNA is interwound, and the probability of spatial site juxtaposition is much higher than in relaxed DNA. We find, however, that supercoiling does not correspondingly increase the rate of juxtaposition at these physiological conditions. An explanation to this unexpected finding emerges on analysis of the juxtaposition dynamics. We note that although a particular site i 1 in supercoiled DNA is often in close proximity (juxtaposed) to another site i 2 , the change of i 2 occurs very slowly and depends largely on internal slithering of opposite segments of the DNA superhelix. Such slithering results in long correlations between successive values of i 2 ; these correlations increase the average time of juxtaposition between two DNA sites. Random collisions between sites located on different superhelix branches—although increasing in importance with DNA size—contribute less substantially to site juxtaposition at high salt than slithering for DNA up to 6 kb in length.